Growth After Adenotonsillectomy for Obstructive Sleep Apnea: Revisited. (22nd September 2021) - Jensen, Alexandria M.; Herrmann, Brian W.; Mitchell, Ron B.; Friedman, Norman R.
Abstract : Objectives/Hypothesis: To reanalyze the growth trajectory and assess longitudinal changes of children undergoing adenotonsillectomy (AT) versus watchful waiting (WW) enrolled in the Childhood Adenotonsillectomy Trial (CHAT) study and to determine if an AT increases the risk of obesity in children. Study Design: Reanalysis of prospective cohort investigation. Methods: The study analyzed publicly available data from CHAT, including 3 months visit data not previously included in a prior publication. Statistical comparisons and mixed‐effects modeling were done using age‐ and sex‐specific BMI expressed as a percentage of the 95th percentile (%BMIp95). P  < .05 was considered significant. Results: Children in the AT group, especially if underweight at baseline, had an increased rate of weight gain, with 100% of underweight children in the AT group becoming normal weight compared to 20% for WW. However, the rate of weight gain, as measured by the %BMIp95 trajectory for both AT and WW groups, was not significantly different when baseline weight status and obstructive sleep apnea (OSA) resolution were accounted for. Comparisons of %BMIp95 between treatment groups at baseline, 3‐ and 7‐month follow‐up visits also failed to identify statistically significant differences ( P  > .05). Overall for the entire cohort, resolution of OSA was associated with a decreased weight trajectory ( P  < .001). Conclusions: AT compared to WW is not associated with an increased risk of excessive weight gain. Otolaryngologists should be aware of this updated analysis when discussing AT surgical outcomes with families. Level of Evidence: 2 Laryngoscope, 132:1289–1294, 2022